2011
DOI: 10.1002/bit.23337
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific biomass recalcitrance in corn stover pretreated with liquid hot‐water: Enzymatic hydrolysis (part 1)

Abstract: Lignin content, composition, distribution as well as cell wall thickness, structures, and type of tissue have a measurable effect on enzymatic hydrolysis of cellulose in lignocellulosic feedstocks. The first part of our work combined compositional analysis, pretreatment and enzyme hydrolysis for fractionated pith, rind, and leaf tissues from a hybrid stay-green corn, in order to identify the role of structural characteristics on enzyme hydrolysis of cell walls. The extent of enzyme hydrolysis follows the seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 36 publications
(44 reference statements)
7
43
0
3
Order By: Relevance
“…The effectiveness of enzymatic hydrolysis of leaf internodes following NaOH pretreatment further suggests that alkaline susceptible cell wall components did not have a differential effect upon leaf cell wall digestibility. Although displaying comparable yields to alkaline pretreated leaf sheaths, leaf cell walls may be more susceptible to a pretreatment that predominantly removes more polysaccharide components, such as liquid hot water pretreatment, which has shown to dramatically improve leaf digestibility [67]. …”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of enzymatic hydrolysis of leaf internodes following NaOH pretreatment further suggests that alkaline susceptible cell wall components did not have a differential effect upon leaf cell wall digestibility. Although displaying comparable yields to alkaline pretreated leaf sheaths, leaf cell walls may be more susceptible to a pretreatment that predominantly removes more polysaccharide components, such as liquid hot water pretreatment, which has shown to dramatically improve leaf digestibility [67]. …”
Section: Discussionmentioning
confidence: 99%
“…Liquid hot water (LHW) pretreatment of corn stover showed pith tissue is more readily hydrolyzed than rind or leaf, and that microscopic changes occur when pretreated corn stover fractions are hydrolyzed. These studies also showed that the microscopic structures themselves do not explain differences in recalcitrance (Zeng et al, ; Zeng et al, ; Zeng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Separating components of corn stalk rind, stalk, and leaves, and using them for different purposes are effective ways to improve the added value of resource utilisation (Zeng et al 2012a(Zeng et al , 2012b. Corn stalk rind, as the main component of corn stalk, and showing similar fibre morphologies as wood, has high mechanical strength and is used as a substitute raw material for timber in producing nonstructural plates (He et al 2016a).…”
Section: Introductionmentioning
confidence: 99%